2022
DOI: 10.3389/fpubh.2022.1047794
|View full text |Cite
|
Sign up to set email alerts
|

Association of metabolic dysfunction-associated fatty liver disease, type 2 diabetes mellitus, and metabolic goal achievement with risk of chronic kidney disease

Abstract: BackgroundAlthough type 2 diabetes mellitus (T2DM) plays a significant role in the association between metabolic dysfunction-associated fatty liver disease (MAFLD) and chronic kidney disease (CKD), how T2DM development and glycemic deterioration affect CKD and its renal function indicators, estimated glomerular filtration rate (eGFR) and urine albumin-to-creatinine ratio (UACR), remains unknown. We aimed to assess the association between MAFLD, along with T2DM, and risk of CKD, and then evaluate the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…15,16 In turn, MAFLD increases the risk and severity of CVD and CKD even more strongly than NAFLD both in individuals with or without diabetes. [17][18][19] Moreover, preliminary data show that MAFLD is also associated with glomerular hyperfiltration in subjects with T2DM 20 or prediabetes and visceral obesity. 21 Together, these two abnormalities might synergistically contribute to the pathogenesis of CKD in these populations.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 In turn, MAFLD increases the risk and severity of CVD and CKD even more strongly than NAFLD both in individuals with or without diabetes. [17][18][19] Moreover, preliminary data show that MAFLD is also associated with glomerular hyperfiltration in subjects with T2DM 20 or prediabetes and visceral obesity. 21 Together, these two abnormalities might synergistically contribute to the pathogenesis of CKD in these populations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, MAFLD has been linked to an elevated risk of cardiovascular disease, compounding the existing burden in individuals with diabetes [9]. Recent study has reported that among persons at risk for MAFLD, persons with T2D pose nearly a three-fold risk of chronic kidney disease [6]. Even more disconcerting, studies have demonstrated that among individuals with MAFLD, those with T2D are at a higher risk of liver-related mortality compared with those without T2D [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…T2D is a major risk factor for MAFLD and a predictor of poor liver-related health outcomes among people living with MAFLD [ 6 , 7 ]. In a previous meta-analysis, researchers found a 55.5% prevalence of MAFLD among individuals with T2D worldwide (compared with the 32.4% in the general population) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%